Characterisation of material and connection behaviour in sheathed cold-formed steel wall systems – Part 1: Experimentation and data compilation. (April 2021) - Kyprianou, Constantinos; Kyvelou, Pinelopi; Gardner, Leroy; Nethercot, David A.
Abstract: The material and connection behaviour in sheathed cold-formed steel wall systems are investigated in the present paper through experimentation. A total of 103 material and component tests was performed, including six cold-formed steel tensile coupon tests, nine tests on screws in tension, nine tests on screws in shear, 36 material tests on plasterboard and orientated strand board (OSB), 25 pull-through connection tests and 18 push-out (shear) connection tests. The plasterboard and oriented strand board were tested in both compression and tension, as well as both longitudinally and transversely to the production direction of the board. The main objective of the study was to measure and characterise the nonlinear response of all the materials and sheathing-to-steel connection components that are used in typical cold-formed steel wall systems, to support the ongoing and future development of accurate numerical simulations and structural design provisions for such systems. The present paper focuses on the experimental investigation and the collection of existing test data from the literature; a description of all the tests performed and a discussion of the results obtained are provided. The companion paper focuses on the establishment and assessment of predictive models to describe the responses of the material and connection components.